CONSTRUÇÃO DE UM TRECHO EXPERIMENTAL COM REUTILIZAÇÃO DO FRESADO ASFÁLTICO NA CAMADA DE BASE - Silva, Carlos F. S. C. e.; Bassani, Luiz A.; Specht, Luciano P.; Echeverria, José A. S. (Salão do Conhecimento, 2013)
Resumo